Adverse event reporting in Slovenia - the influence of safety culture, supervisors and communication - Birk Karin; Pađen Ljubiša; Markič Mirko (Vojnosanitetski Pregled)
Background/Aim. The provision of safe healthcare is considered a priority in European Union (EU) member states. Along with other preventative measures in healthcare, the EU also strives to eliminate the “causes of harm to human health”. The aim of this survey was to determine whether safety culture, supervisors and communication between co-workers influence the number of adverse event reports submitted to the heads of clinical departments and to the management of an institution. Methods. This survey is based on cross-sectional analysis. It was carried out in the largest Slovenian university hospital. We received 235 completed questionnaires. Respondents included professionals in the fields of nursingcare, physiotherapy, occupational therapy and radiological technology. Results. Safety culture influences the number of adverse event reports submitted to the head of a clinical department from the organizational point of view. Supervisors and communication between co-workers do not influence the number of adverse event reports. Conclusion. It can be concluded that neither supervisors nor the level of communication between co-workers influence the frequency of adverse event reporting, while safety culture does influence it from an organizational point of view. The presumed factors only partly influence the number of submitted adverse event reports, thus other causes of under-reporting must be sought elsewhere.